Kriteria Pemimpin Negara Menurut Undang-Undang Dasar 1945 Ditinjau Dari Kriteria Imam Menurut Al-Mawardi - Harmayanti, Halvina; Saebani, Beni Ahmad; Sutiana, Yana (LPPM Universitas Ekasakti Padang, 2024)
A leader is someone who has been chosen by a group who is given the mandate to lead the organization to achieve a goal, and is considered to have an influence on others and has an inherent leadership spirit. In Islam, the criteria for ideal leaders are in the Prophet Muhammad, but as ordinary humans, of course, we cannot equalize the criteria for leaders in the Prophet Muhammad, therefore in Islam there are criteria for imams according to Al-Mawardi which are based on the Qur'an and Hadith. In Indonesia, there are criteria for leaders according to the 1945 Constitution and Law No. 7/2017 on general elections. The two criteria certainly have different views, but if the two are compared whether it will be relevant or contradictory. This study will answer the relevance of the criteria of state leaders in Indonesia with the criteria of the Imam according to Al-Mawardi. This study will answer the relevance of the criteria for state leaders in Indonesia with the criteria for imam according to Al-Mawardi. This type of research belongs to the Qualitative category using descriptive analysis methods with data collection techniques, namely library research or literature studies. The 5 criteria for state leaders according to the 1945 Constitution and Law No. 7 of 2017 are relevant to the criteria for imam according to Al-Mawardi, namely according to the 1945 Constitution and Law No. 7 on elections (never betrayed the country and never committed corruption and other serious crimes, educated at least graduated from high school / vocational or other schools equivalent, spiritually able to carry out the duties of his obligations as President and Vice President and free from narcotics abuse, has a vision, mission, and program in implementing the government of the Republic of Indonesia, and the President is a native Indonesian) and according to Al-Mawardi (fair, healthy, knowledgeable, healthy limbs, have a vision and mission, and descendants of the Quraysh). So it can be concluded that the criteria for state leaders according to the 1945 Constitution and Law No. 7/2017 on elections when compared with the criteria for priests according to Al-Mawardi will be very relevant.